Brachiobasalic Versus Brachiocephalic Arteriovenous Fistula for Vascular Access during Hemodialysis: A Review - Chandrashekhar C Mahakalkar; Suhas N Jajoo; Meghali N Kaple; Shivani Kshirsagar; Melisa Philip; Vaibhav Thorat (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: A functional vascular access site is the lifeline for patients with end stage kidney disease that require chronic hemodialysis. The ground-breaking article by Brescia and Cimino in 1966 revolutionized the creation of the vascular access, and the Cimino fistula was soon used in almost all dialysis patients. Arteriovenous Fistula is an autologous arteriovenous access created by a connection of a vein to an artery where the vein serves as the accessible conduit. The vascular access can be created using Radial artery or Brachial artery. Common locations include the forearm (radiocephalic) and upper arm (brachiocephalic and brachiobasilic). Other less common combinations may exist, such as the ulnar-basilic fistula. When less commonly created vascular access are studied, a clear description of their surgical anastomosis is suggested. Aim: to review Brachiobasalic Versus Brachiocephalic Arteriovenous Fistula for Vascular Access during Hemodialysis. Conclusions: Most of the studies have measured the outcomes in terms of Time-dependent patency, Anatomic patency, Vascular Access Maturation and Complications related to surgical Procedures and Cannulation.